Synthesis of 3-Substituted Chromones and Quinolones from Enaminones - Joussot, Jessie; Schoenfelder, Angèle; Larquetoux, Laurent; Nicolas, Marc; Suffert, Jean; Blond, Gaëlle (Synthesis, 2016)
A facile and efficient synthetic route to 3-substituted chromones and quinolones was developed. Silver triflate was employed to activate the electrophile to react with various readily available enaminones.
Keywords: heterocycles; chromones; quinolones; enaminones; organoselenides; silver salt